The structure of the labour market and wage inequality using RIF-OLS: The Italian case - Giangregorio Luca; Fana Marta (European Commission, Joint Research Centre (JRC), 2021)
This paper aims at identifying how and to what extent the Italian labour market structure in terms of job composition and institutional changes shape the dynamics of wages and wage inequality in the decade 2007-2017. We investigate the main determinants behind the rise in wage inequality in Italy using Recentered Influence Function (RIF) regressions. This econometric approach allows - on one side - to directly assess the effects over the unconditional distribution and on statistics beyond the mean, like the Gini coefficient. On the other, it decomposes the inequality difference into the endow-ment and wage effects, following the standard Oaxaca-Blinder technique. We observe that the occupational structure and institutional changes - contractual arrangements (permanent vs temporary contract) and working time (full-time vs part-time) - are the main factors in explaining the wage downgrade at the bottom of the income distribution and the consequent in-crease in wage inequality.
Keywords: 330; inequality; labour market; wages; RIF